Costs Associated With Geriatric Ankle Fractures: Operative Versus Nonoperative Management. Issue 1 (February 2017) - Kadakia, Rishin J.; Ahearn, Briggs M.; Tenenbaum, Shay; Bariteau, Jason T.
Introduction . Ankle fractures are the third most common orthopaedic injury seen in the geriatric patient. Studies have identified mortality benefits with operative management, but treatment must be considered on a case-by-case basis. In the era of value-based analysis, a thorough of understanding of outcomes and costs of treatment is required. The purpose of this study was to analyze the inpatient and readmission costs associated with operative and nonoperative management of geriatric ankle fractures. Methods . Patients were identified using diagnosis codes for ankle fractures from all 2008 Part A Medicare claims. Patients younger than 65 years and those who sustained an ankle fracture during the previous year were excluded. Operative patients were then identified by ICD-9 procedure codes. Other variables collected included age, comorbidities, and the incidence of hospital readmissions. Inpatient costs were determined using Medicare reimbursement data. Results . A total of 19 648 patients with ankle fractures were identified. Of these, 15 193 (77.3%) underwent operative intervention. The mean cost for initial fracture admission was 5097.20 for nonoperative management compared with 8798.10 for operative management ( P < .05). The mean inpatient costs associated with readmission for nonoperative intervention was 5161.50 and for operative treatment, it was 5071.40 ( P > .05). The reimbursement for hospital readmissions for both groups combined for approximately 29.7 million. The total cost of initial treatment plus readmission for both treatment groups combined was approximately 185 million. Discussion . The total expenditure estimate of 185 million in this study has likely increased given the steady growth of the geriatric population. Expenditures associated with these readmissions was approximately 30 million—nearly a sixth of total costs. Future work must focus on determining which patients will benefit from operative intervention and optimizing care to decrease readmissions and their associated cost in this growing cohort of patients. Levels of Evidence: Therapeutic, Level III: Retrospective study